Screening of Foreign Investments and the Bilateral Investment Treaties of Bangladesh - Hossain, Mohammad Belayet; Yeon, Asmah Laili Bt; Aziz, Ahmad Shamsul Bin Abdul (Society & Sustainability, 2021)
Since 1960, about 2852 bilateral investment treaties (BITs) have been signed. Of them, 2298 BITs are in force at present. In the last 61 years, the WTO members failed to conclude a global treaty to regulate FDI in host countries, consequently, the BITs have played a significant role to regulate FDI. As a member of the WTO, Bangladesh has signed 31 BITs so far with various states to allow and increase the inflow of FDI into the country. Bangladeshi foreign investment laws and BITs mainly protect foreign investors. However, neither of them has any specific provision regarding the screening of foreign investments in Bangladesh. Two questions have been addressed in this paper: (a) Do the BITs of Bangladesh allow the host state for screening of foreign investments at the entry stage? (b) Should the screening of FDI be required during the pre-entry stage in Bangladesh? In this paper, a doctrinal research method has been used to critically analyze 15 BITs to explore whether there is any reference for screening of foreign investments in Bangladesh. We find that the existing Bangladesh BITs have provisions to promote and protect foreign investments but have no reference in relation to the screening of foreign investments. Therefore, the author has recommended that the Government of Bangladesh can consider specific provisions for screening of FDI in future BITs.